Narasi Tragis Dalam Manga : Sebuah Kajian Estetika Aristotelian Terhadap Komik 5 Centimeters per Second: Sebuah Kajian Estetika Aristotelian Terhadap Komik 5 Centimeters per Second - Aditya Nirwana; Evelyne Afriliana Gultom (Lembaga Penelitian Pengembangan dan Pengabdian Kepada Masyarakat STMIK Asia Malang, 2019)
Comics, or in Indonesian, are often referred to as cergam (cerita bergambar), later they have found urgency in the science of art and literature as sequential art, whose existence can be appreciated both in art and literature. This study will highlight literary aspects or ideoplastic aspects of 5 Centimeters per Second, especially in flow and character . The purpose of this study is to reveal or explain how the tragedy was revealed in 5 Centimeters per Second. In achieving these objectives, the theorization in this study was done deductively to answer the research questions. The theory used to explain the problem is the concept of Aristoteles's Tragedy, which relates to his work Poetics as a work of classical Greek philosophy. With an explanation of the flow and the order of comics that have advantages in two respects (visual and literary technical achievements), the results of this study are expected to be a consideration in making comics. The results of this study can be concluded that the manga is present by imitating objects, events, actions, and character in a moral category that is better than humans or the world in general. In addition, in this manga story, almost all the characters (or 'actors' in Aristoteles's terminology) are aware of how to act, they really know but don't do it, eventually sinking into a puddle of suffering. According to Aristoteles, a tragic story like this is the worst.